Drugs affecting blood pressure variability: an update - Höcht, Christian (2015)
Blood pressure variability (BPV) is considered nowadays a novel risk factor for cardiovascular disease. Clinical evidences support that short-term and long-term BPV independently contribute to target organ damage, cardiovascular events and mortality in patients with hypertension or diabetes. Attenuation of excessive fluctuations of systolic and diastolic BPV has been suggested as an additional therapeutic target in cardiovascular prevention. A growing number of preclinical and clinical studies have focused in the assessment of drug effects or other interventions on the different types of BPV and their contribution in the prevention of cardiovascular events. Prospective clinical trials have shown that antihypertensive classes differ in their ability to control excessive BP fluctuations with an impact in clinical outcomes. Current evidences suggest that calcium channel blockers are more effective than other blood pressure lowering drugs for the reduction of short-term, mid-term and long-term BPV. In order to increase actual knowledge regarding the therapeutic significance of BPV in cardiovascular disease, there is a need for additional clinical studies specifically designed for the study of the relevance of short-term and long-term BPV control by antihypertensive drugs